PERANCANGAN TAMAN OLAHRAGA SEBAGAI RUANG TERBUKA PUBLIK DI KOTA KUALA KAPUAS - Astuti, Laila; Saud, Mohammad Ibnu (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The design of this Sports Park is the design of public space with the aim of being a place for recreation and community exercise, as well as to encourage community interest in sports. The design of this sports park is based on the lack of recreational facilities in the City of Kuala Kapuas. The focus of the planning is on recreational and sports activities that are inclusive and can be of interest to the community. Efforts to combine several functions in an area become a problem in this design, so the mix use concept is used as a solution to solving problems with the symbiotic approach method. The concept of mix use is applied as a design program so that it can accommodate many spatial functions while symbiosis is used in the application of designs so that space functions can work and support each other. So that the design results are obtained in the form of Areas with diverse, overlapping, and interconnected functions.